2020
DOI: 10.1097/md.0000000000021862
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Hemiarthroplasty should not be selected as the primary option for intertrochanteric fractures in elderly patients aged 85 years or more

Abstract: This study aimed to compare the early outcome of proximal femoral nail antirotation (PFNA) and bipolar hemiarthroplasty (BPH) in elderly intertrochanteric fractures (ITFs) patients aged 85 years or more. This is a prospective cohort study, and we analyzed 120 elderly patients aged 85 years or more presented with ITFs who underwent BPH and PFNA between January 2017 and July 2018. 84 patients treated with PFNA were set as Group A, and 36 patients treated with BPH were set as Group B. Data such as gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The prolongation of the operation duration and the deterioration of hemodynamics due to bleeding cause an increased need for postoperative intensive care. According to the studies performed, blood loss and blood transfusion need are higher with hemiarthroplasty [17,19]. In our study, when the ratio of patients who needed postoperative intensive care was examined, no significant difference was found between the two groups.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The prolongation of the operation duration and the deterioration of hemodynamics due to bleeding cause an increased need for postoperative intensive care. According to the studies performed, blood loss and blood transfusion need are higher with hemiarthroplasty [17,19]. In our study, when the ratio of patients who needed postoperative intensive care was examined, no significant difference was found between the two groups.…”
Section: Discussionmentioning
confidence: 50%
“…Some studies did not find a significant difference in mortality rates within the first year [12,16]. In the study of Kumar et al [17] and other similar studies [18,19], patients with advanced age were evaluated as in our study, and no significant difference was found between the two groups in terms of mortality in the first year. In our study, the mean day of death in the PFNA group was 88 days, whereas it was 41.5 days in the hemiarthroplasty group (not given in the text).…”
Section: Discussionmentioning
confidence: 55%
“…Mortality rates 12 months after operation in PFNA were similar with BPH and HHS 12 months after operation in PFNA was similar with BPH. [ 21 ] Vestergaard et al found that patients with arthroplasty had a significantly higher mortality rate compared to patients with PFN. [ 22 ] In the meta-analysis of Cui et al on the application of either hemiarthroplasty or internal fixation in the treatment of elderly patients with femoral neck fractures, there was no significant difference between the two treatments in terms of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…So, we may say that the BHA method is a disadvantageous technique for hip fracture repair in general. Tan et al (13) have also reported significantly high postoperative complication and mortality rates in patients who underwent BHA and therefore suggested not to select BHA as a primary option in trochanteric fractures in the elderly. In their systematic review, Kumar et al ( 14) also suggested the PFN method in elderly patients as a safer surgical technique.…”
Section: Discussionmentioning
confidence: 99%